Does Taiwan's entry into the WTO truly reduce its agricultural output values?. Issue 6 (17th August 2016) - Cheng, Chia Yi; Lu, Chen Fu; Chen, Yu Hui
Abstract : This study has used the time series data of Australia, China, Denmark, India, Japan, the Netherlands, Norway, the Philippines, South Korea, Spain, and the United States from the World Bank to estimate the agricultural economic shock of Taiwan's accession to the World Trade Organization (WTO). We have adopted the recently developed panel data approach for policy evaluation to construct the annual agricultural growth path of Taiwan, which is mainly based on the cross-sectional correlations between the domestic and international agricultural trade markets in the absence of Taiwan's entry into the WTO. Our results have not only revealed the importance of ex post counterfactual analysis, but also provided empirical evidence that the agricultural economic shock is not as severe as predicted by many ex ante studies. Based on these results, we have concluded that the outcome may have arisen from the slow progress of achieving agricultural trade liberalization under the WTO and the Taiwanese Government's effective adoption of phase-in periods and relative adjustment policies.